Software database project : project D - Yin, Yuan (Nanyang Technological University, 2020)
School of EEE has an organization called Student Life and Development Unit (SLDU). It was established to ensure that all EEE students receive appropriate academic advice when needed. The Unit’s academic consultants assist students to identify their difficult area and developing strategies to improve students’ academic performance. Students are able to provide information and support regarding study skills, learning strategy, academic prerequisites and coursework expectations. This is an important service provided by the school, helping many students achieve their academic goals. Each year school of EEE will host many events for students, and SLDU intended to build a new tool which would help for better planning of activities for EEE students.The platforms for operating this tool are based on web-app and mobile-app. The mobile app will be used by students for making registration and taking attendance for each event. The web-app will be used by SLDU staffs like event planner for managing event related data, reviewing all the participants and their information, as well as checking for upcoming events. This project is currently assigned to a group of 5 students to develop and it was separated to two parts: web-app and mobile-app. My task was design and implement a dashboard of the SLDU web-app front end. In this project, several website application design principles, programming languages, database setting, and other related technics were investigated and practiced. The whole process will be explained in detail in this report, including introduction, Data visualization, Dashboard design, Dashboard implementation, Result and Discussion, as well as Conclusion and future work recommendation.